Defining Legacy: The Perceptions of Pediatric Health Care Providers. (October 2020) - Boles, Jessika; Jones, Maile; Dunbar, Jenna; Cook, Jessica
Legacy building interventions like plaster hand molds are offered in most children's hospitals, yet little is known about how the concept of legacy is understood and described by pediatric health care providers. Therefore, this study explored pediatric health care providers' perceptions of legacy at an academic medical center to ensure that future legacy interventions are evidence-informed and theoretically grounded. An electronic survey featuring three open-ended questions and two multiple-choice questions with an option for free text response was completed by 172 medical and psychosocial health care providers. Analysis yielded four themes: (1) legacy is intergenerational, enduring, and typically associated with end-of-life; (2) legacies articulate the impacts on others for which one is known and remembered; (3) legacies can be expressed through tangible items or intangible qualities; and (4) legacies are informed and generated by family relationships and work experiences. By understanding legacy as a personally and professionally contextualized experience, health care providers can better assess and meet the legacy needs of hospitalized pediatric patients and families.